OF ALGORITHM AND PROCEDURES OF THE ORGANIZATIONAL AND TECHNICAL METHOD OF THE ABBREVIATION OF NEGATIVE CONSEQUENCES OF EMERGENCY SITUATIONS OF THE MEDICAL AND BIOLOGICAL CHARACTER OF THE LOCAL LEVEL OF DANGEROUS DISTRIBUTION - , Р. І. (Municipal economy of cities. Series: «Economy science», 2018)
The paper considers the process of forming an algorithm and separate procedures for the implementation of the organizational and technical method of reducing the negative consequences of emergency situations of medical and biological character. The above study completes the formalization of theoretical foundations for creating an organizational and technical method for reducing the negative consequences, in particular the number of victims and the number of victims, from emergency situations of medical and biological character, using the previously created apparatus of information and communication influence on complex processes of spreading the consequences of emergencies. This is achieved by providing the basic properties of the algorithm for implementing the method due to: discreteness - high level of detail of the process of obtaining variation parameters; clearness, certainty and effectiveness - an internal mechanism for the harmonization of the suitability of uncontrolled variables of mathematical models for the dependence of the negative consequences of emergencies of medical biology and management decision making models that are global for the entire internal information and communication environment; mass - the mechanism of adaptation of the latter to the information heterogeneity of the internal informational and communicative environment in the conditions of manifestation of the dangers of medical and biological nature of different frequency of occurrence, which in turn encompasses the entire range of threats of medical and biological nature. In turn, the implementation of the procedures of the algorithm for implementing the organizational and technical method of reducing the negative consequences of emergency situations of medical and biological character of the local level of distribution is provided by the synthesis of a number of measures of a technical and organizational nature and subject to conditions: in terms of achieving the completeness of information - reducing the discrepancy between the actual and necessary volume formalized information, in terms of usefulness of information - reduction of information with zero utility and increase of functionality s possibilities of information processing operator in terms of mass algorithm using emergency frequencies different manifestations of risk - interest balance formal and informal information that describes the state of distribution of emergency situations medical and biological nature. Further practical application of the obtained theoretical results will significantly improve the efficiency of the process of formation, transmission and processing of information messages regarding the identification of the sources of danger of medical and biological nature and the spread of the consequences of their impact. Keywords: organizational and technical method, consequences of emergencies, medical and biological hazards